Mitochondrial uncoupler triclosan induces vasorelaxation of rat arteries - Xiyue Zhang; Xinzi Zhang; Yanqiu Zhang; Mingyu Liu; Jing Jin; Jie Yan; Xin Shen; Nan Hu; Deli Dong (Acta Pharmaceutica Sinica B, 2017)
Our previous studies found that mitochondrial uncouplers induced vasodilation. Triclosan, the broad spectrum antibacterial agent, is the active ingredient in soaps and toothpastes. It was reported that triclosan induced mitochondrial uncoupling, so we aim to investigate the effects of triclosan on vascular function of rat mesenteric arteries and aorta. The isometric tension of rat mesenteric artery and thoracic aorta was recorded by multi-wire myograph system. The cytosolic [Ca2+]i, mitochondrial reactive oxygen species (mitoROS), and mitochondrial membrane potential of smooth muscle cells (A10 cells) were measured using laser scanning confocal microscopy. Triclosan treatment relaxed phenylephrine (PE)- and high K+ (KPSS)-induced constriction, and pre-treatment with triclosan inhibited PE- and KPSS-induced constriction of rat mesenteric arteries. In rat thoracic aorta, triclosan also relaxed PE- and KPSS-induced constriction. Triclosan induces vasorelaxation without involving KATP channel activation in smooth muscle cells of arteries. Triclosan treatment increased cytosolic [Ca2+]i, mitochondrial ROS production and depolarized mitochondrial membrane potential in A10 cells. In conclusion, triclosan induces mitochondrial uncoupling in vascular smooth muscle cells and relaxes the constricted rat mesenteric arteries and aorta of rats. The present results suggest that triclosan would indicate vasodilation effect if absorbed excessively in vivo.